2021
DOI: 10.1186/s12889-021-10186-0
|View full text |Cite
|
Sign up to set email alerts
|

The role of sexual compulsivity in unprotected intercourse among STI patients in Shanghai, China

Abstract: Background Sexual compulsivity (SC) and its relationship with unprotected intercourse (UI) have long been an intriguing topic, but its existential meaning in the management of public health or, more precisely, sexually transmitted infections (STIs) has rarely been studied to date. This study examines whether SC plays a role in UI among sexually active STI patients. Method A cross-sectional study was conducted in two sexual transmitted disease (STD)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…When compared to their counterparts, those who did not get any skill training about safer sex behaviors had a 9-fold AOR = 9.00(5.10,15.88) higher chance of developing sexual compulsivity. The findings matched those of studies conducted in the United States and China [ 13 , 36 , 37 ]. Self-awareness, emotional adjustment, and education are all important for managing sexual desires and ritualistic habits.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…When compared to their counterparts, those who did not get any skill training about safer sex behaviors had a 9-fold AOR = 9.00(5.10,15.88) higher chance of developing sexual compulsivity. The findings matched those of studies conducted in the United States and China [ 13 , 36 , 37 ]. Self-awareness, emotional adjustment, and education are all important for managing sexual desires and ritualistic habits.…”
Section: Discussionsupporting
confidence: 84%
“…Therefore, life skill training is essential. Individuals who are well-versed in various safe sexual practices, such as the use of toys, traps, and masturbations, are also important in resolving recurrent sexual impulses, thoughts, and behaviors [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Across studies, CSB seems to be substantially more prevalent in men than in women ( Böthe et al., 2018 ; Dickenson et al., 2018 ). CSB has frequently been investigated in men who have sex with men ( Coleman, 1991 ; Coleman et al, 2010 ; Ni et al., 2021 ) and often in association with sexual risk taking ( Rooney, Tulloch, & Blashill, 2018 ). Sexual urges and the frequency of sexual behavior (e.g., total sexual outlet) are age-dependent ( Peters, Pullman, Kingston, & Lalumière, 2022 ), with CSB being negatively related to age.…”
Section: Introductionmentioning
confidence: 99%
“… 15 Generally, men with high levels of compulsivity and sensation-seeking engage in relationships with multiple partners, 16 have sex under the influence of alcohol, 17 do not use condoms during vaginal or anal intercourse, 18 and have higher STI incidence rates. 19 The study clearly demonstrated a weak but positive relationship between condom knowledge and use. There was also significant mediation of the relationship between condom knowledge and use by condom use attitude.…”
Section: Introductionmentioning
confidence: 84%